Pregunta

Explain how to find the inverse of a quadratic function when graphed and reflect it over the line \( y = x \); provide an example using the function \( h(x) = x^2 - 4 \).

Ask by Reese Hammond. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

To find the inverse of the quadratic function \( h(x) = x^2 - 4 \) for \( x \geq 0 \), swap \( x \) and \( y \) to get \( x = y^2 - 4 \), then solve for \( y \) to find \( y = \sqrt{x + 4} \). This inverse function reflects the original graph over the line \( y = x \).

Solución

To find the inverse of a quadratic function by reflecting its graph over the line \( y = x \), you need to follow a series of steps. Since quadratic functions are **not one-to-one** over their entire domain (they fail the horizontal line test), you'll first need to **restrict the domain** to make the function one-to-one. Let's walk through this process using the function \( h(x) = x^2 - 4 \) as an example. ### Step 1: Understand the Original Function The function \( h(x) = x^2 - 4 \) is a parabola that opens upwards with its vertex at \( (0, -4) \). Its graph is symmetric about the y-axis. ### Step 2: Restrict the Domain To make \( h(x) \) one-to-one, restrict its domain to either \( x \geq 0 \) or \( x \leq 0 \). This ensures that for each \( y \)-value, there's only one corresponding \( x \)-value. **Example Restriction:** Let's choose \( x \geq 0 \). ### Step 3: Reflect the Graph Over \( y = x \) Reflecting a function over the line \( y = x \) effectively swaps the roles of \( x \) and \( y \). To find the inverse: 1. **Start with the original equation:** \[ y = x^2 - 4 \] 2. **Swap \( x \) and \( y \):** \[ x = y^2 - 4 \] 3. **Solve for \( y \):** \[ x + 4 = y^2 \\ y = \sqrt{x + 4} \] *Note:* Since we restricted the domain to \( x \geq 0 \), we take the **positive** square root. ### Step 4: Define the Inverse Function The inverse function is: \[ h^{-1}(x) = \sqrt{x + 4} \] ### Step 5: Verify the Inverse To ensure that \( h^{-1}(x) \) is indeed the inverse, verify that: \[ h(h^{-1}(x)) = x \quad \text{and} \quad h^{-1}(h(x)) = x \] **Verification:** 1. **First Composition:** \[ h(h^{-1}(x)) = h(\sqrt{x + 4}) = (\sqrt{x + 4})^2 - 4 = x + 4 - 4 = x \] 2. **Second Composition:** \[ h^{-1}(h(x)) = h^{-1}(x^2 - 4) = \sqrt{(x^2 - 4) + 4} = \sqrt{x^2} = x \] *Note:* This holds true because \( x \geq 0 \). ### Step 6: Graphical Interpretation - **Original Function \( h(x) = x^2 - 4 \):** A parabola opening upwards with vertex at \( (0, -4) \) and restricted to \( x \geq 0 \). - **Inverse Function \( h^{-1}(x) = \sqrt{x + 4} \):** This is the right half of a sideways parabola, reflecting the original function over the line \( y = x \). When graphed together, these two functions will be mirror images of each other across the line \( y = x \). ### Complete Example **Original Function:** \[ h(x) = x^2 - 4 \quad \text{for} \quad x \geq 0 \] **Finding the Inverse:** 1. **Swap \( x \) and \( y \):** \[ x = y^2 - 4 \] 2. **Solve for \( y \):** \[ y^2 = x + 4 \\ y = \sqrt{x + 4} \] 3. **Inverse Function:** \[ h^{-1}(x) = \sqrt{x + 4} \] **Verification:** - \( h(h^{-1}(x)) = x \) - \( h^{-1}(h(x)) = x \) (since \( x \geq 0 \)) **Graphical Reflection:** - Plot \( h(x) = x^2 - 4 \) (restricted to \( x \geq 0 \)). - Plot \( h^{-1}(x) = \sqrt{x + 4} \). - These graphs will be symmetrical about the line \( y = x \). ### Important Considerations - **Domain Restriction:** Without restricting the domain, the inverse wouldn't be a function because it wouldn't pass the vertical line test after reflection. Always ensure the original function is one-to-one before finding its inverse. - **Choosing Branches:** Depending on the domain restriction (e.g., \( x \geq 0 \) or \( x \leq 0 \)), the inverse will correspondingly take the positive or negative square root. By following these steps, you can successfully find the inverse of any quadratic function by reflecting its graph over the line \( y = x \), provided you properly restrict its domain to ensure it's one-to-one.

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To find the inverse of the quadratic function \( h(x) = x^2 - 4 \), you'll first need to rewrite it in the form of \( y = h(x) \). Then, swap \( x \) and \( y \) to find the inverse: \( x = y^2 - 4 \). Solve for \( y \) by rearranging the equation to get \( y^2 = x + 4 \), and then take the square root, resulting in \( y = \sqrt{x + 4} \) or \( y = -\sqrt{x + 4} \). However, since the original function is not one-to-one over its entire domain, keep it restricted, for example, to \( x \geq 0 \), yielding the inverse \( h^{-1}(x) = \sqrt{x + 4} \). Reflecting this inverse over the line \( y = x \) means creating a visual mirror image of the graph. So for our function, if we were to graph \( h(x) = x^2 - 4 \) and its inverse \( h^{-1}(x) = \sqrt{x + 4} \), you’d see that they symmetrically align with the line \( y = x \). This reflects the relationship between each output of \( h \) and its corresponding input in \( h^{-1} \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad